Planting the Municipal Ownership Idea in Port Arthur, 1875–1914 - High, Steven (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1997)
The municipal ownership idea found fertile soil on the rocky north shore of Lake Superior. The predominance of local land ownership, the absence of large industrial employers and a small population where religion and ethnicity eased potential class differences created a climate conducive to collective action in Port Arthur. The degree of conflict or cooperation that characterized local social relations inevitably extended to the operation of the municipal government and shaped the ways in which citizens perceived their municipality and its role within the community. This was of paramount importance as Ontario municipal law bound the municipal administration to the will of the majority of the taxpayers by requiring that all money by-laws and franchise agreements be voted upon. The accountability feature of the Municipal Act, coupled with a convergence of local interests under the rubric of boosterism, convinced Port Arthur residents to pioneer municipal enterprise in the early 1890s. The creation of one of the first municipally owned and operated electric street railways in the world was the innovation of small-scale land owners disillusioned with the boodling habit of the town's elite. The emerging consensus in favour of municipal enterprise was such that by 1901, not even the formidable Bell Telephone Company could dissuade Port Arthur inhabitants. In the process we see that frontier communities like Port Arthur did not always accommodate the interests of local elites. Instead of a local populace manipulated by the booster rhetoric of businesspeople and land developers, this study reveals a remarkable degree of political accommodation, and even the active cooperation of local ratepayers.